2001
DOI: 10.2514/2.5810
|View full text |Cite
|
Sign up to set email alerts
|

Review of Refractory Materials for Alkali Metal Thermal-to-Electric Conversion Cells

Abstract: Refractory alloys are being considered as structural materials in multitube, vapor-anode alkali metal thermalto-electric conversion (AMTEC) cells for future use in radioisotope space electric power systems. In these power systems, the AMTEC cells would operate at a heat source temperature of » 1150 K and a radiator temperature of » 550 K, for a 7-15 year mission lifetime. In addition to high strength, low density, and low brittle-to-ductile transition temperature, suitable materials must be compatible with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Refractory alloys have high creep strength at high temperatures and excellent compatibility with alkali liquid metals as long as oxygen, nitrogen, carbon, and silicon impurities are kept below appropriate limits, typically in the range of a few to 10Õs ppm [16,17]. For example, Nb-1%Zr suffers embrittlement in as low as 10 ppm oxygen, which detrimentally affects its mechanical properties.…”
Section: Spr-4 [6]mentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory alloys have high creep strength at high temperatures and excellent compatibility with alkali liquid metals as long as oxygen, nitrogen, carbon, and silicon impurities are kept below appropriate limits, typically in the range of a few to 10Õs ppm [16,17]. For example, Nb-1%Zr suffers embrittlement in as low as 10 ppm oxygen, which detrimentally affects its mechanical properties.…”
Section: Spr-4 [6]mentioning
confidence: 99%
“…Molybdenum-rhenium alloys, developed to remedy the lack of ductility of pure molybdenum at low temperatures, and to increase creep strength [19] and the resistance to oxygen embrittlement, are stronger but much heavier than niobium alloys [4,17]. Rhenium increases the re-crystallization temperature of the Mo-Re alloy to 1450-2000 K, depending on the amount of Re (1645 K for Mo-14%Re) [20,21].…”
Section: Spr-4 [6]mentioning
confidence: 99%
“…Other potential corrosion mechanisms of refractory metals and alloys by alkali metals are the chemical reactions with impurities, particularly nonmetallic, such as oxygen, carbon, nitrogen and silicon (Reid et al, 1991;King and El-Genk, 2001). Corrosion failures could also result Table 2 Operation life tests of alkali-metal heat pipes (Merrigan, 1985;Angelo and Buden, 1985;Houts et al, 1998;Rosenfeld et al, 2004).…”
Section: Structural Materials For Heat Pipesmentioning
confidence: 99%
“…The results of life tests conducted at Los Alamos National Laboratory (Ranken, 1982;Merrigan, 1985;Merrigan and Trujillo, 1992;Reid et al, 1991) demonstrated good compatibility of various alkali metals with refractory metals and alloys ( Table 2), provided that oxygen content is kept very low, less than 1-10 ppm (Reid et al, 1991;King and El-Genk, 2001). Niobium and tantalum are particularly susceptible to oxygen attacks in Na containing < 1-10 ppm O 2 .…”
Section: Structural Materials For Heat Pipesmentioning
confidence: 99%
See 1 more Smart Citation